2014
DOI: 10.1016/j.jvs.2014.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Vein Graft Preservation Solutions, Patency, and Outcomes After Coronary Artery Bypass Graft Surgery: Follow-up From PREVENT IV Randomized Clinical Trial

Abstract: Inpatient Register and the Swedish National Register for Vascular Surgery (Swedvasc). Associations were estimated with Cox proportional hazards models. The cohorts included 35,550 women and 42,596 men, aged 46 to 84 years. During follow-up, AAA was identified in 199 women and 958 men. The incidence of AAA per 100,000 person-years was 76 among men who never smoked and 136 among women who currently smoked. Regarding AAA risk, women were more sensitive to current smoking (P interaction ¼ .002). Compared with neve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 0 publications
0
48
0
9
Order By: Relevance
“…1 In this issue of Circulation, Hess and colleagues 2 report insights from the PREVENT IV study on VGF after CABG surgery. This is the 11th study published in a major journal reporting results of the PREVENT IV study [3][4][5][6][7][8][9][10][11][12] and involves the same patients. The angiographic results were analyzed from different clinical angles.…”
Section: The Prevent IV Studymentioning
confidence: 99%
“…1 In this issue of Circulation, Hess and colleagues 2 report insights from the PREVENT IV study on VGF after CABG surgery. This is the 11th study published in a major journal reporting results of the PREVENT IV study [3][4][5][6][7][8][9][10][11][12] and involves the same patients. The angiographic results were analyzed from different clinical angles.…”
Section: The Prevent IV Studymentioning
confidence: 99%
“…The GALA solution (Glutathione, Lascorbique acid, L-arginine and glucose; pH = 7.4), being widely recognized in this purpose; its effects compared to other solutions (saline and autologous blood with added heparin) maintained the endothelial function and structural viability of the grafts for 1 to 24 h of storage [10]. A sub study of the PREVENT IV randomized trial demonstrated that buffered saline solution had lower vein graft failure rate studied by angiography 12 to 18 months after surgery and better clinical outcomes compared to saline or autologous blood solutions [11].…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial integrity is critical to avoid early graft occlusion. During a CABG procedure, there is a routine time interval—usually 1 to 2 hours long—between vein harvesting and SVG to coronary artery anastomosis conduction, when the graft is kept in a storage solution 1,7,8 …”
Section: Introductionmentioning
confidence: 99%
“…This interval may be critical for endothelial integrity and subsequent patency of the graft. Therefore, graft patency partially depends on the composition and temperature of the storage solution 1,7,8 . There is an endless debate as to which storage solution is optimal.…”
Section: Introductionmentioning
confidence: 99%